2014
DOI: 10.1103/physrevd.90.055005
|View full text |Cite
|
Sign up to set email alerts
|

125 GeV Higgs signal at the LHC in theCP-violating MSSM

Abstract: The ATLAS and CMS collaborations have observed independently at the Large Hadron Collider (LHC) a new Higgs-like particle with a mass M h ∼ 125 GeV and properties similar to that predicted by the Standard Model (SM). Although the measurements indicate that this Higgs-like boson is compatible with the SM hypothesis, however due to large uncertainties in some of the Higgs detection channels, one still has the possibility of testing this object as being a candidate for some Beyond the SM (BSM) physics scenarios, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 170 publications
0
12
0
Order By: Relevance
“…As for case (2), taking into account that the charged Higgs mass is limited to be above 200 GeV (see e.g. [99,132] and references therein) the fact that its loop contribution is suppressed by a factor of (M W /M H ± ) 2 and thatĝ hH + H − is of the order of the electroweak coupling (contrary to theĝ hSS coupling for squarks and sleptons which can be large as we discuss below), we have found that the contribution from charged Higgs bosons is generally negligible. In case (3), the chargino contribution can be bigger than that of the charged Higgs, because of the ratio F 1/2 : F 0 ≃ 4 and because the chargino has a lower mass limit of approximately 100 GeV (coming from LEP2 [133]).…”
Section: Via Charged Higgs Boson Contributionsmentioning
confidence: 99%
“…As for case (2), taking into account that the charged Higgs mass is limited to be above 200 GeV (see e.g. [99,132] and references therein) the fact that its loop contribution is suppressed by a factor of (M W /M H ± ) 2 and thatĝ hH + H − is of the order of the electroweak coupling (contrary to theĝ hSS coupling for squarks and sleptons which can be large as we discuss below), we have found that the contribution from charged Higgs bosons is generally negligible. In case (3), the chargino contribution can be bigger than that of the charged Higgs, because of the ratio F 1/2 : F 0 ≃ 4 and because the chargino has a lower mass limit of approximately 100 GeV (coming from LEP2 [133]).…”
Section: Via Charged Higgs Boson Contributionsmentioning
confidence: 99%
“…It was shown in [108][109][110] that CP violation does not have important consequences on the dark matter sector after imposing the experimental constraints from the electric dipole moments and the Higgs coupling measurements, so that the results presented in the following will remain valid also for CP violating scenarios. We impose the lightest neutralino to be the lightest supersymmetric particle which constitutes dark matter, using the set-up presented in [111,112].…”
Section: Mssm Scansmentioning
confidence: 98%
“…Inclusion of CP violation in the Higgs sector of such models allows CP-mixed physical scalars. The phenomenology of such a possibility has been considered in the literature [26][27][28][29][30]. In a recent study [31], it has been pointed out that the ILC is an ideal setting to probe the CP nature of the Higgs boson in the process considered here.…”
Section: Introductionmentioning
confidence: 99%